2020
DOI: 10.1109/access.2020.3029501
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Factors That Influence Offshore Outsourcing Decision of Application Maintenance

Abstract: Application maintenance consumes a considerable amount of an organization's time and resources each year. Almost 60% of IT budget is spent alone on application maintenance. The reason of offshore outsourcing of application maintenance is not only the reduction of maintenance cost but to free up the resources and to keep the focus on core products. Offshore outsourcing is a common business strategy that is used by companies to achieve cost savings about 20-50%. However, the decision making process of applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 37 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…The adoption of hybrid methodology aims to thoroughly investigate the research domain. We have already performed a systematic literature review [1] that identified a list of influencing factors concerning the offshore outsourcing decisions of application maintenance. The current study, evaluates the findings of the systematic literature review in the outsourcing industry.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The adoption of hybrid methodology aims to thoroughly investigate the research domain. We have already performed a systematic literature review [1] that identified a list of influencing factors concerning the offshore outsourcing decisions of application maintenance. The current study, evaluates the findings of the systematic literature review in the outsourcing industry.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Since, it follows a pre-defined research review protocol, it therefore, differs from an ordinary review [37]. A new study protocol was developed and followed for the identification of influencing factors concerning offshore outsourcing decision of application maintenance that was published in [1], [2]. The systematic literature reviews were carried out by adopting the guidelines of Kitchenham [37].…”
Section: A Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…e DSS applications are evidenced in different areas of life. Such applications include the DSS in agriculture, business, energy, and so on [4][5][6][7][8][9][10][11][12][13][14][15]. Numerous domains and applications have explored methods and theories regarding decision-making for alternatives including from simple to advance, intelligent, and smart systems [16,17].…”
Section: Introductionmentioning
confidence: 99%